Can Adopt AI‐Powered Educational Technology Buffer Against Academic Stress and School Burnout? A Protective Model Proposal - Küçükaydın, Menşure Alkış (Psychology in the schools, 2025)
This study examined the relationship between trust in AI‐powered educational technology (AI‐EdTech) and school burnout among Turkish high school students and the mediating role of perceived usefulness and academic stress in this relationship. A total of 619 students ( M age = 15.95, SD = 0.94) participated in the study, and structural equation modeling was used. In the tested model, trust in AI‐EdTech was found to directly and negatively affect school burnout. However, perceived usefulness and academic stress were not significant mediators. In contrast, the serial mediation mechanism was found to be substantial, i.e., significant relationships were found between trust in AI‐EdTech and perceived usefulness and between academic stress and school burnout. These results suggest that students' confidence in AI‐EdTech systems leads them to perceive these systems as more practical and thus may reduce burnout through reduced academic stress. However, the inability of perceived usefulness or academic stress to mediate alone suggests that these two variables are effective when they work together. The results indicate that for AI‐EdTech to be used efficiently in education, strategies to increase student's confidence and practices that emphasize the usefulness of the systems and reduce academic stress should be developed. Trust in AI‐EdTech negatively predicts school burnout. Perceived usefulness and academic stress mediate together. AI‐EdTech trust reduces burnout via lower academic stress.